Dengue: muscle biopsy findings in 15 patients - S.M.F. Malheiros; A.S.B. Oliveira; B. Schmidt; J.G. Camargo Lima; A.A. Gabbai (Arquivos de Neuro-Psiquiatria)
Dengue is known to produce a syndrome involving muscles, tendons and joints. The hallmark of this syndrome is severe myalgia but includes fever, cutaneous rash, and headache. The neuromuscular aspects of this infection are outlined only in isolated reports, and the muscle histopathological features during myalgia have not been described. In order to ascertain the actual neuromuscular involvement in dengue and better comprehend the histological nature of myalgia, we performed a clinical and neurological evaluation, a serum CPK level and a muscle biopsy (with histochemistry) in 15 patients (4 males), median age 23 years (range 14-47) with classic dengue fever, serologically confirmed, during the bra-zilian dengue epidemics from September 1986 to March 1987. All patients had a history of fever, headache and severe myalgia. Upon examination 4 had a cutaneous rash, 3 had fever, and 3 a small hepatomegaly. The neurological examination was unremarkable in all and included a manual muscle test. CPK was mildly elevated in only 3 patients. Muscle biopsy revealed a light to moderate perivascular mononuclear infiltrate in 12 patients and lipid accumulation in 11. Mild mitochondrial proliferation was seen in 3, few central nuclei in 3, rare foci of myonecrosis in 3, and 2 patients had type grouping. Dengue in our patients, produced myalgia but no detectable muscle weakness or other neuromuscular involvement. The main histopathological correlation with myalgia seems to be a perivascular mononuclear infiltrate and lipid accumulation.